DEVELOPMENT OF SPEECH OF JUNIOR SCHOOLCHILDREN AS PSYCHOLOGICAL AND PEDAGOGICAL THIS METHODOLOGICAL PROBLEM - N.I. Bilokonna (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the problem of speech development of junior schoolchildren; the different scientific approaches are analysed; the ways of language skills perfection of schoolchildren are suggested.